The enlightened capitalists - O'Toole, James (New York Harper Business, 2019)
Today's business leaders are increasingly pressured by citizens, consumers, and government officials to address urgent social and environmental issues. Although some corporate executives remain deaf to such calls, over the last two centuries, a handful of business leaders in America and Britain have attempted to create business organizations that were both profitable and socially responsible.
Includes bibliographical references and index.
Keywords: Businesspeople--United States--Biography.